Slope stability monitoring using GSM network system - Omar R.C.; Taha H.; Khalid N.H.N.; Roslan R.; Baharuddin I.N.Z.; Ahmad F. (International Association of Lowland Technology, 2023)
Groundwater; Human resource management; Losses; Monitoring; Slope protection; System stability; Early Warning System; Electronic sensors; Geological formation; Geotechnical instruments; Hydrological condition; Slope instability; Slope monitoring system; Stability monitoring; Slope stability; early warning system; maintenance; monitoring system; risk assessment; slope failure; slope stability